Consequences of Ethnic and Madhesh Movements of Nepal - Dhakal, Sedunath (KMC Research Journal, 2017)
This paper explores on the consequences of ethnic and regional conflicts in Nepal, and also clarifies about how the recognition of Madheshi people deferred after the Madhesh movement -2015. Conflict has really created the misunderstanding and gap to split the deep and long time relationship among different ethnic and regional people living harmoniously in Nepal since long in its history. It has also changed the attitudes and perspectives of Nepali people to look at India and China, Nepal’s two neighbours. Further it made Nepal as a state able to rethink about alternatives for lessening dependency and to step ahead for strengthening its sovereignty.